Assistência à autonomia domiciliar empregando paradigma orientado a notificações - Oliveira, Rodrigo Nunes (2019)
The rising in life expectancy is reflected in an increase in the elderly population and numerous actions become necessary to ensure the elderly a proper quality of life and independence in performing daily tasks. One of the applications of the Internet of Things technology (IoT) is the creation of smart environments with interactive devices allowing integration between the physical environment and the individual. A viable application of intelligent environments is the Ambient Assisted Living (AAL), which can enable elderly and people with some kind of limitations be assisted in their daily routine, independently and safely. In this context, in order to provide assistive technology, this research aims to create an AAL system that can be extended to new scenarios and that use parallel resources naturally, distributed resources and business modeling through environment rules. To do só, was choose to use the Notification Oriented Paradigm (PON). Thus, for implementation of the AAL system applying PON, Raspberry Pi microcomputers are used, which are responsible for communicating with the physical sensors and actuators of the environment, and for controlling notifications distributed among the various controllers present in the same residence. Also, it had required the creation of three other systems: a website, responsible for the integration among all parts of the solution as well as the management and persistence of all the environments’ configuration and their respective rules; a mobile app for monitoring and controlling the environment, and the people included in it; and lastly, a simulator that simulates rules and sensors in a virtual environment. The final system implementation was assessed qualitatively, by means of PON compliance analysis with AAL system requirements; and quantitatively by its performance in processing activities such as sensor reading, PON internal notifications and network notifications. Using PON, it was possible to create an extensible AAL solution, as it allows the inclusion of new sensors and reconfiguration of their rules in real time, as well as monitoring the environment through the constant use of parallelism and distributed processing.